2010
DOI: 10.1039/b920025h
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile-functionalized pyrrolidinium ionic liquids as solvents for cross-coupling reactions involving in situ generated nanoparticlecatalyst reservoirs

Abstract: A series of nitrile-functionalized pyrrolidinium-based ionic liquids have been prepared and characterized by spectroscopic methods and X-ray crystallography. The application of these new ionic liquids as reaction media for Suzuki and Stille C-C cross-coupling reactions has been investigated and compared with related imidazolium and pyridinium systems (including those with and without nitrile functionalities). The nature of the ionic liquid strongly influences the catalyzed reaction and it would appear that, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…[1][2][3][4] ILs have unique and tuneable properties useful in the synthesis of MNPs via chemical routes. This can be controlled simply by incorporating coordinating groups, [5][6][7] varying the coordination strength of the anion, 8,9 or changing the length of the alkyl-chain in the cation. [10][11][12][13][14][15] In general, appropriate metal complexes or metal salts are dispersed/dissolved in the IL and subsequently reduced to the corresponding M-NPs, in the ubiquitous presence of reducing reagents such as molecular hydrogen gas, complex hydrides (NaBH 4 and LiAlH 4 ), hydrazine, 1-4 alcohols, 16 and thiols.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] ILs have unique and tuneable properties useful in the synthesis of MNPs via chemical routes. This can be controlled simply by incorporating coordinating groups, [5][6][7] varying the coordination strength of the anion, 8,9 or changing the length of the alkyl-chain in the cation. [10][11][12][13][14][15] In general, appropriate metal complexes or metal salts are dispersed/dissolved in the IL and subsequently reduced to the corresponding M-NPs, in the ubiquitous presence of reducing reagents such as molecular hydrogen gas, complex hydrides (NaBH 4 and LiAlH 4 ), hydrazine, 1-4 alcohols, 16 and thiols.…”
Section: Introductionmentioning
confidence: 99%
“…Tailoring the ion structures gives access to the tuning of the properties of the ILs [30][31][32][33][34]. Thus, it is possible to design ILs with defined hydrophilicity or hydrophobicity, viscosity as well as coordinating properties.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…It was demonstrated that nitrile-functionalised ILs are superior for Pd-NP stabilisation to non-functionalised ILs (Figure 2). (Zhao et al, 2004;Chiappe et al, 2006;Fei et al, 2007;Cui et al, 2010) Moreover, tetraalkylammonium bromides are also suitable as reaction medium for the Stille reaction with Pd-NPs catalysts. A library of imidazolium, pyridinium and pyrrolidinium ILs with nitrile groups was designed to improve prolonged catalyst lifetime in the Stille reaction, among other crosscoupling reactions.…”
Section: Stille Reactionmentioning
confidence: 99%
“…A library of imidazolium, pyridinium and pyrrolidinium ILs with nitrile groups was designed to improve prolonged catalyst lifetime in the Stille reaction, among other crosscoupling reactions. (Zhao et al, 2004 Zhao et al, 2004;Chiappe et al, 2006;Fei et al, 2007;Cui et al, 2010) In these works an anion-dependence was described using pyridinium ILs with palladium chloride as precursor. It is a direct approach to various molecular palladium species with cations and anions in the coordinating sphere of the palladium.…”
Section: Stille Reactionmentioning
confidence: 99%